Conceptual Metaphor of “Quality” in Charles & Keith’s Marketing: A Cognitive Semantic Analysis - Silalahi, Elisa Debora (Lingua Susastra, 2024)
This research presents a cognitive semantics study in Charles Keith's Instagram caption. It is conducted to observe the conceptual metaphors of “quality” in Charles Keith's Instagram caption, including the types and image schema of each conceptual metaphor. The data source is Charles Keith's Instagram caption uploaded in January 2023 – June 2023. The research used a qualitative method with a cognitive semantics approach. Based on the analysis, there are 10 conceptual metaphors of “quality” classified into three types of conceptual metaphors: 5 structural metaphors, 2 orientational metaphors, and 3 ontological metaphors. Moreover, 3 metaphors belong to the image schema of identity, 3 metaphors belong to the image schema of force, 2 metaphors belong to the image schema of space, and 2 metaphors belong to the image schema of existence. Those conceptual metaphors are utilized to highlight the quality of Charles Keith products by portraying the products’ excellence.